The ecology of waste water treatment - Hawkes, H. A. (Herbert Aubrey) (Pergamon Press, 1963)
"The Ecology of Waste Water Treatment covers the principles of biology considered necessary for an understanding of some ecological aspects of wastewater treatment. This book is composed of seven chapters, and begins with an overview of the significant biological aspects related to wastewater treatment. The subsequent chapters examine the factors determining the dominant organisms in sludge and bacteria beds. Other chapters highlight the role of biological oxidation in wastewater treatment and the ecological parameters in the design and operation of activated sludge plants. A chapter provides practical methods of maintaining population balance at a low level of microorganisms. The final chapter considers the operational requirements necessary to ensure suitable ecological conditions for bacteria beds. This book is of value to microbiologists, ecologists, and environment-related fields."